The Impact Of Visual Thinking On Teaching Students Some Basic Basketball Skills - Ali Khalaf Mousa (Penerbit Jurnal Indonesia, 2026)
The study aims to develop instructional units based on the visual thinking approach and to examine their effect on learning complex offensive skills in basketball among students. The researcher adopted an experimental method due to its suitability for the nature of the research problem. An equivalent groups design with pre- and post-tests was employed. The research population consisted of first-year students in the morning study program at the College of Physical Education and Sports Sciences, University of Misan, for the academic year 2025–2026. Two sections were randomly selected to represent the main research sample: Section (B) as the experimental group and Section (A) as the control group. The main sample included 40 students, with 20 students in each group, while 10 students from Section (B) were selected for the pilot sample. The main sample constituted 22.48% of the total population. Pre- and post-tests for the basketball skills under investigation were conducted, and the data were statistically analyzed using the SPSS package. The findings revealed the superiority of the experimental group, which was exposed to instructional units designed وفق the visual thinking approach, over the control group that was taught using the conventional method. This superiority was clearly reflected in the level of skill acquisition. The improvement is attributed to the role of the visual thinking strategy in actively engaging students in the learning process and in organizing and interpreting information visually, thereby enhancing motor understanding and linking the stages of skill performance within a coherent framework. The researcher concluded that adopting the visual thinking approach in teaching basketball skills contributes to improving the level of skill learning and enhances the student’s role as the core of the educational process. The study recommends integrating this approach into basketball instructional units and conducting further research to compare its effectiveness with other teaching strategies in order to identify the most impactful methods for developing skill performance and promoting students’ thinking through visual learning.